Effectiveness of RAD Method On E-Commerce Based Sales System PT Battuta Jaya Center - Chairul Imam; Muhammad Furqon Siregar (Politeknik Ganesha Medan, 2024)
This research was conducted with the aim of building a sales information system in the raw publisher PT Battuta Jaya Center and to assist company management in providing sales. The system This web-based sales information system was built using Freamwork Codeigniter 3.1.0, Php MySql, Xampp, Adobe Illustrator and Blackbox Testing Method to test the system system. That way the result of this research is a sales information system that is used to transactions, purchases and recording sales reports that are more computerized, efficient and accurate. computerized, efficient and accurate.